2021
DOI: 10.1002/ps.6717
|View full text |Cite
|
Sign up to set email alerts
|

Fall armyworm in Botswana: impacts, farmer management practices and implications for sustainable pest management

Abstract: BACKGROUND: Since first reported in Botswana, fall armyworm (FAW) continues to be a threat to crop production. This study aimed to estimate impacts of FAW on yield and farmers' livelihoods in Botswana, and to obtain data that could be extrapolated to national level. Further, farmer knowledge of the pest, management practices and pesticide use for FAW management were assessed. RESULTS: In fact, 76% of the 220 respondents had seen FAW in their farms in the 2018/2019 cropping season, affecting almost the entire a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
(21 reference statements)
1
7
1
Order By: Relevance
“…Against the background variance caused by differences in soils and plot management, we were unable to detect any significant effect of S. frugiperda infestation, or leaf damage on yield. These results are in stark contrast to many other reports from the region, including from Malawi and Zambia, that have tended to suggest very high levels of yield loss caused by S. frugiperda ( Kansiime et al 2019 , De Groote et al 2020 , Kassie et al 2020 , Abro et al 2021 , Tambo et al 2021 , Kwasi et al 2022 , Makale et al 2022 ). How can we reconcile these very different findings?…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Against the background variance caused by differences in soils and plot management, we were unable to detect any significant effect of S. frugiperda infestation, or leaf damage on yield. These results are in stark contrast to many other reports from the region, including from Malawi and Zambia, that have tended to suggest very high levels of yield loss caused by S. frugiperda ( Kansiime et al 2019 , De Groote et al 2020 , Kassie et al 2020 , Abro et al 2021 , Tambo et al 2021 , Kwasi et al 2022 , Makale et al 2022 ). How can we reconcile these very different findings?…”
Section: Discussioncontrasting
confidence: 99%
“…Since its arrival in sub-Saharan Africa, there have been a number of reports concerning the impacts of S. frugiperda . Most have suggested that these impacts are substantial ( Kansiime et al 2019 , De Groote et al 2020 , Kassie et al 2020 , Abro et al 2021 , Tambo et al 2021 , Kwasi et al 2022 , Makale et al 2022 ). For example, based on household surveys, Tambo et al (2021) reported that severe infestations caused a 44% reduction in household income and a 17% increased likelihood of experiencing hunger in Zimbabwe.…”
mentioning
confidence: 99%
“…The FAW is one of most important global migratory crop pests originally found in tropical/subtropical regions of the America but has recently spread rapidly to other parts of the world. In this study, we wanted to determine a method to enhance pest control with RNAi by improving the stability and RNAi delivery efficiency of dsRNA. We selected methoprene-tolerant gene ( Met ) of the FAW as a target gene, critical to the growth and development of the pest. First, we selected three potential dsRNA fragments, approximately 500 bp in length, and determined the efficiency of these dsRNA on expression level of the Met gene.…”
Section: Introductionmentioning
confidence: 99%
“…The fall armyworm (FAW), Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae), is a notorious worldwide agricultural pest originating in the Americas, has long-distance migration capacity, omnivorous behavior, and high fecundity, and developed resistance to various insecticides . As a polyphagous insect, S.…”
Section: Introductionmentioning
confidence: 99%
“…The fall armyworm (FAW), Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae), is a notorious worldwide agricultural pest originating in the Americas, has long-distance migration capacity, omnivorous behavior, and high fecundity, and developed resistance to various insecticides. 1 As a polyphagous insect, S. frugiperda larvae feed on 353 species of 42 genera, including maize and rice. 2 Since the invasion of Yunnan from Myanmar in December 2018, S. frugiperda has spread rapidly and posed a serious threat to food security in China.…”
Section: Introductionmentioning
confidence: 99%